The Value of believing in yourself : the story of Louis Pasteur - Johnson, Spencer (La Jolla, CA : Value Comm., Inc. Pub, 1976)
Retells the story of Louis Pasteur, whose unwavering belief in the concept of germs led to a cure for rabies.
Keywords: Pasteur, Louis, 1822-1895; Scientists; Self-reliance -- Juvenile literature; Bacteriologists -- France -- Biography -- Juvenile literature